2021
DOI: 10.1101/2021.03.08.434518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Transcriptional Activity and Diverse Functional Repertoires of Hundreds of Giant Viruses in a Coastal Marine System

Abstract: Viruses belonging to the Nucleocytoviricota phylum are globally distributed and include members with notably large genomes with complex functional repertoires. Recent studies have shown that these viruses are particularly diverse and abundant in marine systems, but the magnitude of actively replicating Nucleocytoviricota present in ocean habitats remains unclear. In this study, we compiled a curated database of 2,431 Nucleocytoviricota genomes and used it to examine the gene expression of these viruses in a 2.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 113 publications
(140 reference statements)
1
5
0
Order By: Relevance
“…The Algavirales is a sister lineage to the Imitervirales that contains 4 families encompassing several well-studied algal viruses. The Prasinoviridae (AG_01) is a family that includes viruses known to infect the prasinophyte genera Bathycoccus, Micromonas, and Ostreococcus [7], and cultivation-independent surveys have provided evidence that the MAGs in this clade are also associated with prasinophytes [36]. Similarly, our approach yielded a well-defined Phycodnaviridae family (AG_02) composed mostly of chloroviruses, consistent with the similar host range of these viruses [37].…”
Section: An Hierarchical Taxonomy For Nucleocytoviricotasupporting
confidence: 64%
“…The Algavirales is a sister lineage to the Imitervirales that contains 4 families encompassing several well-studied algal viruses. The Prasinoviridae (AG_01) is a family that includes viruses known to infect the prasinophyte genera Bathycoccus, Micromonas, and Ostreococcus [7], and cultivation-independent surveys have provided evidence that the MAGs in this clade are also associated with prasinophytes [36]. Similarly, our approach yielded a well-defined Phycodnaviridae family (AG_02) composed mostly of chloroviruses, consistent with the similar host range of these viruses [37].…”
Section: An Hierarchical Taxonomy For Nucleocytoviricotasupporting
confidence: 64%
“…We identified myosin-related genes in a total of 24 NCLDV MAGs (out of 2,275 considered in our survey) by performing BLASTP against reference myosin sequences compiled from a previous study ( Odronitz and Kollmar, 2007 ), through our own independent effort from a parallel environmental genomic survey ( Ha et al, 2021 ). These NCLDV MAGs were derived from the large cellular size fractions of Tara Oceans ( n = 10) and studies by Moniruzzaman et al (2020) ( n = 5) and Schulz et al (2020) ( n = 9).…”
Section: Resultsmentioning
confidence: 99%
“…This observation underlined the fact that viral production requires a greater production of energy by the infected cells. Further, active glycolysis and tricarboxylic acid cycles were identified by metagenomic studies (Moniruzzaman et al, 2020a;Ha et al, 2021) and some proteins were also found in Pandoravirus (Aherfi et al, 2020) and could have a confirmed functional activity such as the isocitrate dehydrogenase protein. Concerning the predicted ATPase subunit A, it is also present in some Klosneuvirinae.…”
Section: Discussionmentioning
confidence: 98%